Turkish Youth in the European Knowledge Economy: Exploring their responses to Europe and the role of social class and school dynamics for their identities - Faas, Daniel (My University, 2007)
Globalisation and Europeanisation are complementary and partly overlapping processes that identify the increasingly supranational context in which political and educational systems are operating. This article explores how Turkish youth in two German and English secondary schools relate to the European knowledge economy, and how their political identities are shaped by school dynamics (ethos, curriculum and peer cultures) and social class positioning. Drawing upon mainly qualitative data, the paper indicates that when the concept of Europe is allied to multiculturalism, there is the possibility of including minority ethnic groups like the Turkish Muslims and giving them the opportunity of relating to the European knowledge economy. If, however, Europe is understood as a white Christian concept, then Turkish teenagers will struggle to relate positively to Europe as a political identity. The article not only gives voice to young Turkish Muslims in Europe but also assesses the potential for Europe to be a common ground for all youth to negotiate their identities.
PUBLISHED
Keywords: Knowledge economy; Turkish youth; Social class; Political identities; Identities in Transformation; Inclusive Society; International Integration